Commodity Outlook 2003: Southeast U.S. Fresh Vegetable Market - Allen F. Wysocki; John J. Vansickle (EDIS, 2003)
This is EDIS document FE373, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2003.